PENGGUNAAN METODE JIGSAW UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SEJARAH POKOK BAHASAN PERKEMBANGAN PEMERINTAHAN ORDE BARU SISWA KELAS XII IPS SMA NEGERI 10 PEKANBARU - Zun Nurani (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2019)
This research is a classroom action research. Using the Jigsaw Method to improve the activities and Learning Outcomes XII IPS (Social science) Students of SMA 10 Pekanbaru. The porpuse of this research is to improve activities and learning outcomes conducted in two cycles. Before conducting the learning process a test is administered, namely the cycle of total scores (2390); cycle I (2885), and cycle II (3070). For the average pre-cycle score was 68.29, the first cycle increased to 78.92, and the second cycle increased to 87.71. The results obtained based on criterion of Minimal Completness 80. The score of completeness in the complete pre-cycle is only 8 students (22.86%), not complete was 27 students (77.14%). In the first cycle there were 24 students who got complete score (68.57%, and 11 students who got uncompleted score (31.43%). In the second cycle there were 34 students who got complete score (97.14%) and uncomplete score was 2.86%. The score based on the range is the highest with 85 and the lowest one with 45; the first cycle with the highest 95 and the lowest based on the range and criterion score, on the cycle the percentage is 31,43% (enough); the first cycle was very high with 37.14 % and the second cycle was very high at 51.43%. For student activities each cycle increased, namely cycle 1reached to 71.43 and cycle II reached to 85.71.